Monosomy 7 in donor cell-derived leukemia after bone marrow transplantation for severe aplastic anemia: report of a new case and review of the literature - Luize Otero; Daiane Correa de Souza; Rita de Cássia Tavares; Bernadete Evangelho Gomes; Telma França Padilha; Luiz Fernando Bouzas; Teresa de Souza Fernandez; Eliana Abdelhay (Genetics and Molecular Biology, 2012)
Monosomy 7 arises as a recurrent chromosome aberration in donor cell leukemia after hematopoietic stem cell transplantation. We report a new case of donor cell leukemia with monosomy 7 following HLA-identical allogenic bone marrow transplantation for severe aplastic anemia (SAA). The male patient received a bone marrow graft from his sister, and monosomy 7 was detected only in the XX donor cells, 34 months after transplantation. The patient's bone marrow microenvironment may have played a role in the leukemic transformation of the donor hematopoietic cells.